Depression among Women Diagnosed with Breast Cancer: A Study from North India - Thakur, Monika; Gupta, Bandna; Kumar, Rohitash; Mishra, Anand Kumar; Gupta, Sameer; Kar, Sujita Kumar (Indian Journal of Medical and Paediatric Oncology, 2019)
Introduction: Major depressive disorder is a major mental health problem and is the fourth most important cause of loss of disability-adjusted life years worldwide. Aim: The study aimed to assess the association of depression among women diagnosed with breast cancer. Methodology: A descriptive, cross-sectional study was done on 102 females diagnosed with breast cancer. Women were recruited using purposive sampling technique. Patients were evaluated on Mini International Neuropsychiatric Interview Version 6.0.0 to screen other psychiatric comorbidities. Hamilton depression 17-item, rating scale was used to measure severity of depression. Results: The prevalence of depression was 47.05% in women diagnosed with breast cancer. Majority of the patients (54.1%) had mild depression. Correlations of clinical and Sociodemographic variables with parameters of depression were not significant. Conclusions: Depression is commonly associated psychiatric morbidity in patients diagnosed with breast cancer. The severity of depression is independent of the sociodemographic and clinical variables of patients with breast cancer.
Keywords: Breast cancer; depression; India; women